Bu-Gu-Sheng-Sui decoction promotes osteogenesis via activating the ERK/Smad signaling pathways - Liu, Ning; Qi, Baoyu; Zhang, Yili; Fang, Shengjie; Sun, Chuanrui; Li, Qiuyue; Wei, Xu (Frontiers in Pharmacology, 2022)
Osteoporosis is a systemic metabolic skeletal disease, which becomes a common public health problem that seriously endangers people’s health. At present, most of the drugs used to treat osteoporosis have significant side effects, so it is important to find effective anti-osteoporosis medications without major side effects. Bu-Gu-Sheng-Sui decoction (BGSSD) is a safe and effective Chinese medicine formulation for the treatment of osteoporosis. Numerous studies have indicated that it played a significant role in bone anabolism. However, the underlying mechanism remains unclear. Herein, we selected senescence-accelerated mice prone 6 (SAMP6) and MC3T3-E1 cells to study the effects of BGSSD on osteogenesis, then investigated the potential mechanism of BGSSD in treating senile osteoporosis. Our research found that BGSSD protected the bone mass and microstructure in SAMP6, which was reflected in enhanced bone mineral density, increased the expression of osteogenic specific factor Runx2, and improved bone trabecular structure. In vitro, BGSSD accelerated the proliferation and differentiation of MC3T3-E1 cells, which was characterized by stimulating the activity of Alkaline phosphatase (ALP) and raising the expression of Runx2. Moreover, Western blotting and Real-time PCR analysis showed that BGSSD could effectively boost the expression levels of Smad and ERK in vitro and in vivo. Therefore, we speculate that BGSSD may promote bone formation through ERK/Smad pathways. Collectively, our results highlight the importance of BGSSD as a compound in promoting osteogenic differentiation and osteogenesis, demonstrating that BGSSD may become a latent drug to prevent and treat osteoporosis.